2012
DOI: 10.1016/j.jhydrol.2012.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Complex land cover change, water and sediment yield in a degraded Andean environment

Abstract: Exotic forest plantations Hydrology Water yield s u m m a r yRapid land use/-cover change has increasingly transformed the hydrological functioning of tropical Andean ecosystems. The hydrological response to forest cover change strongly depends on the initial state of the ecosystem. Relatively little is known about human-disturbed ecosystems where forest plantations have been established on highly degraded land. In this paper, we analyze the impact of forest change on water and sediment fluxes for a highly deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
2
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 42 publications
2
43
2
10
Order By: Relevance
“…They pointed out that base flow increase was due to reduced evapotranspiration losses following the removal of native forest, and their (native forest) subsequent replacement by grass and crops. Therefore the findings of this study are not in agreement with those of Molina et al (2012). This is an example regarding the conflicting evidence on the impact of forest cover change on dry season flows.…”
Section: Changes In Wet and Dry Season Flows (Peak Vs Low Flows)contrasting
confidence: 89%
See 1 more Smart Citation
“…They pointed out that base flow increase was due to reduced evapotranspiration losses following the removal of native forest, and their (native forest) subsequent replacement by grass and crops. Therefore the findings of this study are not in agreement with those of Molina et al (2012). This is an example regarding the conflicting evidence on the impact of forest cover change on dry season flows.…”
Section: Changes In Wet and Dry Season Flows (Peak Vs Low Flows)contrasting
confidence: 89%
“…Elsewhere, scholars such as Molina et al (2012) observed an increase in dry season flows after deforestation, while at Chongwe 5025 in this study, these flows have decreased significantly in the period with high deforestation. Molina et al (2012) attributed the increase in dry season flows to the increase in base flow after deforestation. They pointed out that base flow increase was due to reduced evapotranspiration losses following the removal of native forest, and their (native forest) subsequent replacement by grass and crops.…”
Section: Changes In Wet and Dry Season Flows (Peak Vs Low Flows)mentioning
confidence: 45%
“…Direct anthropogenic impact associated with land cover change is rapidly transforming the hydrological functioning of tropical Andean ecosystems (Vanacker et al, 2003;Farley et al, 2004;Molina et al, 2012;Harden et al, 2013). The hydrological response is diverse, as changes in vegetation affect various components of the hydrological cycle including evapotranspiration (Nosetto et al, 2005), infiltration (Molina et al, 2007), and surface runoff (Bathurst et al, 2011;Restrepo et al, 2015).…”
Section: A Molina Et Al: Multidecadal Change In Streamflow Associatmentioning
confidence: 99%
“…A full coverage of aerial photographs at the scale of 1/60000 was obtained for November 1963 and1977, and land cover mapping was realized following the orthorectification procedure described by Molina et al (2012). Three Landsat scenes (1991,2001,2009, from the same season) with 1T level of pre-processing were acquired from the USGS (U.S. Geological Survey) archive, and images were atmospherically and topographically corrected with ATCOR3 (Atmospheric and Topographic Correction; Balthazar et al, 2012).…”
Section: Land Cover Change Detectionmentioning
confidence: 99%
“…Different land cover histories assess the effect of land use change on the erosion process. Additionally, changes in the area and crop yield distribution can relate to increases in runoff (Molina et al 2012). Inputs of pollutants in different zones help to establish critical areas of land management.…”
Section: Introductionmentioning
confidence: 99%